The relationship of the legislative system to attracting investment in the banking sector - Guezouli, Abderrahim (The International tax journal, 2025)
The banking system is the cornerstone of the economic sector and a destination for national and foreign investments, through the possibility of opening banks subject to Algerian law, branches of foreign banks, etc. Since these types of banking institutions monopolize the process of receiving funds from the public, etc., it is important that they have a precise legal system, including, in particular, the conditions that must be met to practice the banking profession and the procedures that must be fulfilled from licensing to accreditation.